2012
DOI: 10.1542/peds.2011-2248
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the School Environment on the Emotional Health of Adolescents: A Systematic Review

Abstract: There is limited evidence that the school environment has a major influence on adolescent mental health, although student perceptions of teacher support and school connectedness are associated with better emotional health. More studies measuring school-level factors are needed. Randomized controlled trials evaluating 1 or 2 environmental components may have more success in establishing effective and feasible interventions compared with complex whole-school programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
181
3
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 223 publications
(206 citation statements)
references
References 85 publications
(74 reference statements)
12
181
3
10
Order By: Relevance
“…An unconditional multilevel model indicated that depressive symptoms varied significantly at the individual and school levels, although the proportion of total variation observed at the school level was fairly modest (intraclass correlation 1 = 3.3%). This is consistent with previous studies 17 and does not preclude explaining school-level variation in depressive symptoms by relevant level-2 factors. Table 2 shows the results of longitudinal multilevel models examining the association between school socioeducational environment in grade 8 and student depressive symptoms in grades 10 to 11.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…An unconditional multilevel model indicated that depressive symptoms varied significantly at the individual and school levels, although the proportion of total variation observed at the school level was fairly modest (intraclass correlation 1 = 3.3%). This is consistent with previous studies 17 and does not preclude explaining school-level variation in depressive symptoms by relevant level-2 factors. Table 2 shows the results of longitudinal multilevel models examining the association between school socioeducational environment in grade 8 and student depressive symptoms in grades 10 to 11.…”
Section: Discussionsupporting
confidence: 93%
“…Although we found relatively modest school-level variation in depressive symptoms (intraclass correlation = 3.3%) consistent with estimates reported in previous studies, 17 school socioeducational environment emerged as the strongest predictor of this variation beyond multiple school and individual factors, including previous depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations